2019
DOI: 10.3390/ijms20143397
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Bacterial Effect of CpG-DNA Involves Enhancement of the Complement Systems

Abstract: CpG-DNA activates the host immune system to resist bacterial infections. In this study, we examined the protective effect of CpG-DNA in mice against Escherichia coli (E. coli) K1 infection. Administration of CpG-DNA increased the survival of mice after E. coli K1 infection, which reduces the numbers of bacteria in the organs. Pre-injection of mice with CpG-DNA before E. coli K1 infection increased the levels of the complement C3 but not C3a and C3b. The survival of the mice after E. coli K1 infection was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Polysialic acid-containing residues in the K1 capsule increase binding of complement control protein factor H to C3b molecules in the bacteria surface, which mediates decay-dissociation of amplification C3 convertase (Fearon, 1978;Pluschke et al, 1983). Nevertheless, even though K1 capsule makes the strain more resistant to the bactericidal activity of complement, depletion of C3 using cobra venom factor before infection causes a high mortality rate in the mice against E. coli K1 infection, indicating that C3 has protective functions against E. coli K1 (Kim et al, 2019). Our findings also showed that survival of NMEC in the CSF from C3 À/À mice was much higher than that from the wild-type mice (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysialic acid-containing residues in the K1 capsule increase binding of complement control protein factor H to C3b molecules in the bacteria surface, which mediates decay-dissociation of amplification C3 convertase (Fearon, 1978;Pluschke et al, 1983). Nevertheless, even though K1 capsule makes the strain more resistant to the bactericidal activity of complement, depletion of C3 using cobra venom factor before infection causes a high mortality rate in the mice against E. coli K1 infection, indicating that C3 has protective functions against E. coli K1 (Kim et al, 2019). Our findings also showed that survival of NMEC in the CSF from C3 À/À mice was much higher than that from the wild-type mice (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Besides LPS, another major component of the bacterial envelope of NMEC is K1 capsule, which provides protection against C3mediated killing (Fearon, 1978;Pluschke et al, 1983). However, a previous study identified that depletion of C3 causes a high mortality rate in the mice during E. coli K1 infection, suggesting a role of C3 in controlling E. coli K1 infection in vivo (Kim et al, 2019). It is unclear how microglia and astrocytes react to bacterial invasion and whether C3 plays a role in resisting NMEC invasion in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial DNA is enriched in the unmethylated CpG oligonucleotides (ODN) inducing the differentiation and proliferation of the different types of cells (including endothelial cells, monocytes, neutrophils, dendritic cells, and macrophages), regulating the Th1‐related cytokines production, activates the TLR9‐dependent complement, and triggers the innate immune responses 38,39 . According to reports, CpG‐DNA affects complement activation and regulates the immune system by upregulating the CD3, CD40, and CD83 and inducing cytokines (IL‐6 and TNF‐α), throughout the blood circulation system 40,41 . The DNA of the lactic acid bacteria promotes the TH1 response, promoting stimulation of the immune system probably due to the presence of unmethylated CpG motifs in the bacterial DNA, which are known to trigger TH1‐type immune responses by activating the toll‐like receptor 9 42 .…”
Section: Activation Of the Inflammasomesmentioning
confidence: 99%
“… 38 , 39 According to reports, CpG‐DNA affects complement activation and regulates the immune system by upregulating the CD3, CD40, and CD83 and inducing cytokines (IL‐6 and TNF‐α), throughout the blood circulation system. 40 , 41 The DNA of the lactic acid bacteria promotes the TH1 response, promoting stimulation of the immune system probably due to the presence of unmethylated CpG motifs in the bacterial DNA, which are known to trigger TH1‐type immune responses by activating the toll‐like receptor 9. 42 Studies have shown that the Bifidobacterium genome contains numerous conserved CpG motifs with immunostimulatory activity, but the distribution of these motifs varies in the inter‐and intra‐specific manner.…”
Section: Activation Of the Inflammasomesmentioning
confidence: 99%
“…After 72 h of acclimation in an animal biosafety level 2 facility, seven-to eight-week-old mice were intraperitoneally administered the indicated doses of DA 3 times every alternate day and then intravenously infected with 5 × 10 7 or 1 × 10 8 CFUs of MRSA. At 8 h postinfection, the liver, lung, and kidney were isolated after cardiac perfusion and weighed followed by mechanical homogenization [36]. Briefly, the organs were immersed in 1 mL PBS and homogenized by steel beads using TissueLyser II (QIAGEN, Hilden, Germany).…”
Section: Micementioning
confidence: 99%